Makna Kebahagiaan Menurut Filsafat Kristen : Meraih Kebahagiaan Abadi Dalam Tuhan - Fatieli Halawa; Mozes Lawalata (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
In Christian philosophy, the concept of happiness is often associated with the close relationship between humans and God. Eternal happiness is seen as the highest goal that can be achieved by being loyal to God, experiencing spiritual healing and living according to the principles of the Christian religion. This article explains that happiness in a Christian context includes inner peace, gratitude and the hope of eternal life with God. This analysis emphasizes the importance of faith, prayer and devotion to others to achieve eternal happiness. In addition, this article also emphasizes that true happiness is not only based on material achievements or physical pleasures, but rather on a spiritual connection with God and the fulfillment of a spiritual calling. Thus, the meaning of happiness in Christian philosophy refers to seeking and experiencing eternal happiness in the presence and love of God.